Mucin networks: Dynamic structural assemblies controlling mucus function. (April 2023) - Fass, Deborah; Thornton, David J.
Abstract: Contrary to first appearances, mucus structural biology is not an oxymoron. Though mucus hydrogels derive their characteristics largely from intrinsically disordered, heavily glycosylated polypeptide segments, the secreted mucin glycoproteins that constitute mucus undergo an orderly assembly process controlled by folded domains at their termini. Recent structural studies revealed how mucin complexes promote disulphide-mediated polymerization to produce the mucus gel scaffold. Additional protein–protein and protein-glycan interactions likely tune the mesoscale properties, stability, and activities of mucins. Evidence is emerging that even intrinsically disordered glycosylated segments have specific structural roles in the production and properties of mucus. Though soft-matter biophysical approaches to understanding mucus remain highly relevant, high-resolution structural studies of mucins and other mucus components are providing new perspectives on these vital, protective hydrogels.